(untitled) (Fiep Bulletin - online, 2013)
The benefits of regular practice of physical activity as well as the maintenance of adequate levels of physical fitness are evident. And cardiorespiratory fitness, muscular resistênciaforça, flexibility and body composition components of physical fitness are associated with better performance in activities of daily living (ADL ’s) (DAVIS et al., 2008). It is believed that the regular practice of capoeira mode is able to alter the levels of physical fitness as well as promote physical changes your practitioner, as this is considered a vigorous activity according to the mode for sale by professionals in the field. The improvement in the quality of life of its practitioners as the best performance of the functionality of these in avds are expected. Subjects, between 19 and 55 years of age, of both sexes, were practitioners of capoeira, members of two groups headquartered in the municipality of Rio de Janeiro. The Group generally featured BMI of 25.49 4.05, which means that, on average, the group as a whole is classified as overweight. with respect to the WHR the entire group presented low risk of developing diseases, not showing a significant reduction in the value of the index between the subgroups, and not addition, which may indicate, at least, the maintenance of low risk for developing cardiovascular disease.The practice of capoeira as physical activity seems to be effective to bring its practitioners benefits such as reducing body fat and increasing lean body mass, and seem important for the maintenance of the low risk of developing cardiovascular diseases.